2018
DOI: 10.4097/kja.d.18.27185
|View full text |Cite
|
Sign up to set email alerts
|

Simplified equation for determining proper depth of peripherally inserted central catheter in relation to anatomical landmarks

Abstract: BackgroundThe aim of this study was to develop a formula guiding the peripherally inserted central catheter (PICC) tip placement based on anatomical landmarks such as the upper arm, clavicle, and sternum as well as the patient’s height, weight, and body mass index.MethodsFifty-five patients who were scheduled to have PICCs were included in the study. We measured four distances along the passage of the PICC, which were as follows; the tip of the third finger to the middle of the elbow crease (Distance A), the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, most of the current studies focus on adult PICC positioning formula. Sang‐soo Kang et al derived an adult PICC catheter positioning formula based on anatomical landmarks such as the upper arm, clavicle and sternum as well as the patient’s height, weight and body mass index 18 . The newborn has the characteristics of great difference in height and weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the current studies focus on adult PICC positioning formula. Sang‐soo Kang et al derived an adult PICC catheter positioning formula based on anatomical landmarks such as the upper arm, clavicle and sternum as well as the patient’s height, weight and body mass index 18 . The newborn has the characteristics of great difference in height and weight.…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies have suggested various methods for estimating the ideal position of the central catheter tip, and most agree that the optimal target is the “cavoatrial junction.” Many studies have offered methods to predict optimal catheter length in the situation of blind bedside PICC insertion without fluoroscopy. Among these, PICC length was predicted using bone and soft-tissue landmarks, 2224 while others used patient height. 11,12,25,26 Some studies introduced the VBU method and suggested that 2.0–2.4 VBU below the carina is a reliable estimate of the position of the cavoatrial junction.…”
Section: Discussionmentioning
confidence: 99%
“…Several other methods have been suggested to determine the optimal insertion length of central catheters [7,[13][14][15]. Most of these methods, however, are based on demographic data, may not be intuitive, and/or require complicated intraoperative calculations.…”
Section: Discussionmentioning
confidence: 99%